Pharmacological basis of the antifibrotic effects of pirfenidone: Mechanistic insights from cardiac in-vitro and in-vivo models - Sartiani, Laura; Bartolucci, Gianluca; Pallecchi, Marco; Spinelli, Valentina; Cerbai, Elisabetta (Frontiers in Cardiovascular Medicine, 2022)
Pirfenidone is a small drug with marked antifibrotic activity approved for the treatment of Idiopathic pulmonary fibrosis. Recently, its peculiar pharmacological profile has attracted attention for its potential therapeutic benefit for extra-pulmonary disorders characterized by pathological fibrosis, such as kidney, liver, and cardiac failure. A major pitfall of pirfenidone is the lack of consistent understanding of its mechanism of action, regardless of the target. In addition to the increasing attention to the role of inflammation and its mediators in several processes, a better knowledge of the variety of fibroblasts' population, of signals controlling their activation and trans-differentiation, and of crosstalk with other cell resident and non-resident cell types is needed for prevention, treatment and possibly reverse of fibrosis. This review will focus on pirfenidone's pharmacological profile and its effects on cardiac fibroblasts.